Blue rubber bleb nevus syndrome: a rare presentation of late-onset anemia and lower gastrointestinal bleeding without cutaneous manifestations. Issue 1 (1st January 2016) - Goud, Aditya; Abdelqader, Abdelhai; Walters, Jamie; Selinger, Stephen
Abstract : Blue rubber bleb nevus syndrome (BRBNS) is a congenital disorder with characteristic venous anomalies that can present with varying degree of blood loss. The most clinically significant symptoms in adults include gastrointestinal (GI) bleeding and iron deficiency anemia. Severe complications can include intestinal torsion, intussusception, and even perforation, with each leading to significant morbidity and mortality. This report serves to give a brief understanding of this rare disease along with current diagnostic and therapeutic options.